2021
DOI: 10.1177/03635465211044146
|View full text |Cite
|
Sign up to set email alerts
|

Association of Preoperative Tibial Varus Deformity With Joint Line Orientation and Clinical Outcome After Open-Wedge High Tibial Osteotomy for Medial Compartment Osteoarthritis: A Propensity Score–Matched Analysis

Abstract: Background: The correction of lower limb deformity should be performed at the site of deformity to maintain knee joint orientation. However, the effectiveness of open-wedge high tibial osteotomy (OWHTO) for treatment of medial osteoarthritis in varus malalignment without definite tibial varus deformity has not been confirmed. Purpose/Hypothesis: This study aimed to compare the clinical and radiologic outcomes after OWHTO in patients without tibial varus deformity versus patients with tibial varus deformity aft… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 23 publications
1
17
0
Order By: Relevance
“…Numerous studies have reported that OWHTO showed excellent clinical outcomes, slowed osteoarthritis progression, and delayed subsequent knee arthroplasty. 6,14,24,33,34…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Numerous studies have reported that OWHTO showed excellent clinical outcomes, slowed osteoarthritis progression, and delayed subsequent knee arthroplasty. 6,14,24,33,34…”
mentioning
confidence: 99%
“…Numerous studies have reported that OWHTO showed excellent clinical outcomes, slowed osteoarthritis progression, and delayed subsequent knee arthroplasty. 6,14,24,33,34 Conventionally, the target of adjusting the mechanical axis of the lower extremity is to pass through 62% to 62.5% from the medial edge of the proximal tibia, and previous studies reported favorable clinical outcomes and regeneration of articular cartilage of the medial femoral condyle after OWHTO targeting this point. 7,15,17 Despite accurate preoperative planning and fine surgical techniques, many OWHTOs result in under-or overcorrected alignment of the lower extremity as compared with the target point.…”
mentioning
confidence: 99%
“…To compare the isolated effect of the type of osteotomy relatively independent from confounders, baseline variables were equalized between the 2 groups via propensity score matching, a tool for causal inference in nonrandomized studies allowing for adjustment of covariates. For the matching, the following clinically relevant potentially confounding covariates were chosen as previously proposed in the setting of alignment-correcting osteotomies 19 , 31 : age at surgery, sex, body mass index (BMI), preoperative mechanical femorotibial axis, and time interval since surgery.…”
Section: Methodsmentioning
confidence: 99%
“…The medial proximal tibial angle (MPTA) was defined as the angle between the tibial mechanical axis and articular surface of the proximal tibia. 29 , 33 , 40 The tibial slope was measured as the angle between the line perpendicular to the middiaphysis of the tibia and the line depicting the posterior inclination of the tibial plateau in the lateral view. 23 The medial joint space width was measured from the center of the MFC to the center of the MTP on the Rosenberg view, as described in a previous study.…”
Section: Methodsmentioning
confidence: 99%